2005
DOI: 10.1292/jvms.67.349
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Chronic Wasting Disease in Sika Deer, Cervus nippon, from Tokachi District in Hokkaido

Abstract: ABSTRACT. Surveillance of chronic wasting disease (CWD) was conducted by performing Western blot analysis of tissue samples from 136 sika deer (Cervus nippon) killed by hunters in the Tokachi district of Hokkaido Island. No prion protein (PrP Sc ) associated with CWD was detected in any of the samples. To assess amino acid polymorphisms of the sika deer PrP gene, nucleotide sequencing of the PrP gene was performed. The only amino acid polymorphisms detected were 3 silent mutations at nucleotide positions 63, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
5
12
0
Order By: Relevance
“…22 However, no cases of CWD have been reported in Brazil. The absence of registered cases of CWD-positive animals despite the existence of susceptibility-related genotypes was also identified by Kataoka et al 25 in Cervus nippon. Therefore, the presence of the susceptibility-associated genotypes and the lack of infected animal records in Brazil are of interest because it suggests new putative threats for the conservation of these animals in the Neotropics.…”
Section: Introductionsupporting
confidence: 56%
“…22 However, no cases of CWD have been reported in Brazil. The absence of registered cases of CWD-positive animals despite the existence of susceptibility-related genotypes was also identified by Kataoka et al 25 in Cervus nippon. Therefore, the presence of the susceptibility-associated genotypes and the lack of infected animal records in Brazil are of interest because it suggests new putative threats for the conservation of these animals in the Neotropics.…”
Section: Introductionsupporting
confidence: 56%
“…It has been reported that mAb 44B1 reacts with cervid PrP C , but its reactivity against the authentic PrP Sc of CWD has not been examined (8). In the present study, we demonstrated that mAb 44B1 and other antibodies are able to detect the PrP Sc of CWD (Table 2).…”
Section: (Cervus Nippon Centralis and Cervus Nippon Yesoensis)supporting
confidence: 55%
“…Excluding these cases, it is remarkable that CWD has not been detected outside of North America, unlike scrapie of sheep or bovine spongiform encephalopathy (BSE) of cattle with cases reported virtually worldwide. Active screening efforts thus far have not detected CWD in wild cervids in Belgium, Germany, Japan, and other countries (De Bosschere et al , 2006; Kataoka et al , 2005; Schettler et al , 2006; Schwaiger et al , 2004). Wildlife management efforts to contain or eradicate CWD in Wisconsin or Colorado, where this disease is particularly widespread, have so far proven unsuccessful (Conner et al , 2007; Samuel, 2007).…”
Section: Introductionmentioning
confidence: 99%